2007
DOI: 10.1016/j.jpainsymman.2006.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Prevalence and Severity of Side Effects Based on Type of Analgesic Prescription in Patients with Chronic Cancer Pain

Abstract: An understanding of the relationship between the type of analgesic prescription and the prevalence and severity of side effects is crucial in making appropriate treatment decisions. The purposes of this study were: to determine if there were differences in the prevalence of side effects among four different types of analgesic prescriptions (i.e., no opioid, only an as needed (PRN) opioid, only an around-the-clock (ATC) opioid, or an ATC + PRN opioid); to determine if there were differences in the severity of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…These factors include, but are not limited to, advanced age, female gender, opioid strength/type, reduced mobility, dehydration, hypercalcemia, altered nutritional intake, anal fissures and mechanical obstruction of the bowel [15][16][17][18][19].…”
Section: Opioid-induced Constipationmentioning
confidence: 99%
“…These factors include, but are not limited to, advanced age, female gender, opioid strength/type, reduced mobility, dehydration, hypercalcemia, altered nutritional intake, anal fissures and mechanical obstruction of the bowel [15][16][17][18][19].…”
Section: Opioid-induced Constipationmentioning
confidence: 99%
“…It has been suggested that constipation is the most bothersome side effect, both in terms of its impact on daily life and the frequency of occurrence 54,55 , but nausea and vomiting have been described as highly distressing by patients, sufficient to make them reduce their opioid dose or stop taking it completely 56,57 . Sedation affects between 20% and 70% of patients receiving opioids 58 , but patients may also experience other CNS side effects including cognitive and psychomotor impairment, hallucinations, and toxic effects on neurons, such as hyperalgesia and analgesic tolerance 53 . Less frequently reported are pruritus, respiratory depression, immunological suppression and hormonal changes.…”
Section: Side Effects and The Vicious Circlementioning
confidence: 99%
“…The major reasons for discontinuation of opioid analgesic treatment are gastrointestinal (GI) side effects (i.e., nausea, vomiting, and constipation) along with central nervous system side effects [12]. The incidence of nausea and vomiting reported in patients treated with opioids for chronic pain in a clinical trial setting ranges from 10% to 50% [13–16]. While other GI side effects of opioids such as constipation can be prevented and controlled to some degree by various measures such as laxatives, increased fiber consumption and stool softeners [11], nausea and vomiting effects are more difficult to control fully in the majority of patients [17].…”
Section: Introductionmentioning
confidence: 99%